Hubungan Antara Kecerdasan Emosi dengan Pencapaian Akademik Pelajar di Daerah Hulu Terengganu - Rohaizad, Nor Aizal Akmal; Mislan, Nora (Sains Humanika, 2012)
This research study aims to investigate the level of emotional intelligence between students of Form One in high schools at Hulu Terengganu district in Malaysia. Terengganu district was choosen as the research location because of the proud in academic achivement. The students in Terengganu was made the best record ten years continuesly in primary school test (UPSR) level. The instrument used is a questionnaire which have 95 questions was distributed to 364 Form One students at four high schools in that district. Research outcome showed that the students’ emotional intelligence level is in the medium range. However, between the five domains of emotional intelligence, interpersonal skill is the most dominant domain among the students. Through Pearson correlation analysis, it shows non-significant relationship between the emotional intelligence and the students’ academic achievement. As a conclusion, cooperation between parents and teachers is needed to enhance the students emotional intelligent level to achieve a good academic achivement.